Body size, sex and high philopatry influence the use of agricultural land by Galapagos giant tortoises. Issue 1 (8th January 2022) - Pike, Kyana N.; Blake, Stephen; Cabrera, Freddy; Gordon, Iain J.; Schwarzkopf, Lin
Abstract: As agricultural areas expand, interactions between wild animals and farmland are increasing. Understanding the nature of such interactions is vital to inform the management of human–wildlife coexistence. We investigated patterns of space use of two Critically Endangered Galapagos tortoise species, Chelonoidis porteri and Chelonoidis donfaustoi, on privately owned and agricultural land (hereafter farms) on Santa Cruz Island, where a human–wildlife conflict is emerging. We used GPS data from 45 tortoises tracked for up to 9 years, and data on farm characteristics, to identify factors that influence tortoise movement and habitat use in the agricultural zone. Sixty-nine per cent of tagged tortoises used the agricultural zone, where they remained for a mean of 150 days before returning to the national park. Large male tortoises were more likely to use farms for longer periods than female and smaller individuals. Tortoises were philopatric (mean overlap of farmland visits = 88.7 ± SE 2.9%), on average visiting four farms and occupying a mean seasonal range of 2.9 ± SE 0.3 ha. We discuss the characteristics of farm use by tortoises, and its implications for tortoise conservation and coexistence with people.